Airborne Environmental Threats to Health & Wellness-An Integrated Overview - Safdar Ashraf, Prof. (Dr.) S. M. (International Journal of Medical Science and Clinical Research Studies, 2022)
Background: The environmental pollution is a growing world problem specifically in developed & developing countries. In these areas G.I.T disorders & diarrheal diseases have replaced by airborne environmental disorders.Methods: Literatures was reviewed on the subject to find out the knowledge regarding Environmental threats of air pollution & its effects on the health of human body. Data and details have been located, selected, extracted and synthesized from different national & international Journals, websites, Proceedings, books, google scholar etc.Result & Conclusion: Changes are taking place in air regularly. Different pollutants are being created from different sources. Indoor air pollution is common among underdeveloped & developing nations. To improve health situation different professional, have to play their roles. Effects of air pollution are sometimes general in nature otherwise may be immediate or delayed. Leading causes of death is cardiovascular diseases like IHD are now being declared as airborne. Emergent airborne diseases are more than 30 like COVID 19 only result in 43.6 lakhs death so far. Toxic & hazardous chemicals are present in air in the form of allergens, neurotoxin, mutagen, carcinogen etc. Air pollutants are carbon monoxide, nitrogen oxides, Benzene, Ozone, Lead, sulphates, SPM etc. Meteorological effects on health are also related with air including season, atmospheric pressure, heat, cold etc. Indoor air pollutants have also specific health effects